ELIZA ORZESZKOWA’S WORKS IN THE RECEPTION OF UKRAINIAN WRITERS: CONNECTIONS AND ARTISTIC EXPERIENCE - Spatar, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Aim. This article aims to investigate the reception of Eliza Orzeszkowa’s literary-critical heritage in the works of Ukrainian women writers of the second half of the 19th century, namely Olena Pchilka, Lesia Ukrainka, and N. Kobrynska, who developed the literary-critical discourse about the Polish author’s work, singling out the main ideological and thematic vectors in her work, such as patriotism of the Polish people who were defeated in the January Uprising of 1863, the manifestation of the Jewish question, the woman question, and emancipatory ideas. Olena Pchilka’s manuscript "A word about Eliza Ozheshko at the Ukrainian Club in Kyiv", Lesya Ukrainka’s article "Notes about the Latest Polish Literature" are analyzed, attention is drawn to critical reviews of the Polish author’s emancipatory ideas in N. Kobrynska’s "Autobiography". Methods. A number of main scientific research methods, including historical-literary, typological, and biographical approaches are used for comparative analysis. Results. Through a comparative analysis, the Ukrainian women writers’ works are analyzed, and the main problematic and thematic dominants of Eliza Orzeszkowa’s literary-critical heritage are determined in the context of her artistic-aesthetic and ideological views. Scientific novelty. An attempt is made to analyze the receptions of Eliza Orzeszkowa’s literary-critical heritage in the Ukrainian women writers’ works.